The Cross-Border Enforcement of Court Settlements within Brussels Ia Regulation: From a European and an Austrian Perspective - Anzenberger, Philipp (LeXonomica, 2020)
Despite the enormous practical relevance of court settlements, the Brussels Ia Regulation contains only a few explicit provisions for the cross-border enforcement of this legal instrument. This can cause difficulties in borderline cases, for example when it is doubtful whether the legal act in question is to be classified as a settlement or a judgment or which specific European regulation is applicable to a settlement containing several different claims. This paper provides a general overview of the rules for the enforcement of court settlements under the Brussels Ia Regulation and examines some problems that may specifically arise in the case of cross-border enforcement of court settlements.